IMPLEMENTASI METODE TARGHIB DAN TARHIB DALAM PENDIDIKAN AKIDAH DAN AKHLAK - Sudarto, Sudarto (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2021)
Educating requires ways and methods that can help students absorb and understand the material and teaching delivered by educators. The importance and necessity of Targhib and Tarhib methods in the world of education for its practitioners cannot be completely ignored. Moral aqidah material at MTs Hidayatus Syubban is an educational program directed at encouraging, guiding, and fostering students so that they can know, understand, live and believe in faith so that it colors their daily mindset and behavior. But in general, students are not interested in the material so that in learning the moral creed it is considered normal and underestimated, eventually the teachers complain and that is the same as experienced in other MTs. With this problem, the implementation of the Targhib and Tarhib methods becomes interesting to study. This study aims to describe the implementation of the Targhib and Tarhib methods in learning Akidah Akhlak students of MTs Hidayatus Syubban Karangroto Genuk Semarang. Based on field observations, in Akhlak Akidah Learning the teacher has implemented educational tools in the form of Targhib and Tarhib according to existing theories. Rewards given to students are not in the form of valuable objects, but in the form of words, beautiful praise and deeds. The application of punishment aims so that students know their mistakes and can change them and will not repeat the mistakes they have made. Keywords: Implementation, method, targhib, tarhib